Kristallographische Daten und Schwingungsspektren einiger Oxoapatite der Seltenen Erden des Typs Ca₈Ln₂(PO₄)₆O₂ - Escobar, Marta E. (1982)
Crystallographic data for the oxoapatites of general formula Ca₈Ln₂(PO₄)₆O₂ withLn=La, Pr-Ho) have been obtained from X-ray powder data. The vibrational spectra, which are also discussed, allow to make a proposal about the location of the lanthanide cations present in these lattices.